Security Supply Chain Using UAVs: Validation and Development of a UAV-Based Model for Qatar’s Mega Sporting Events - Khalifa AL-Dosari (17931434) (2023)
Unmanned aircraft vehicles (UAVs) are now used to support security precautions in search and rescue operations to track and evaluate critical services, to provide cybersecurity measures by transporting security supply chain management (SCM) to sports events, and to aid efforts to safeguard the spectators from attacks. A drone may quickly fly over sports grounds, scan the area for potential dangers, and offer aerial footage and still photographs. Although UAVs provide benefits to their operators, there is a possibility that they may also pose cybersecurity threats. This guide offers recommendations for best security practices, intending to assist sports operators in protecting their networks, materials, and staff for Qatar’s mega sporting events. The literature comprises several theoretical frameworks and conceptual models for security supply chains. Unfortunately, there is no practical model for measuring the behavioral intentions of professional IT and security experts. Therefore, this study conducted research in two stages. In the first stage, an in-depth systematic literature review was conducted to identify the factors and themes of UAV-based SCM for security measures. In the second phase, a survey questionnaire (N = 712) was implemented, comprising the themes and items from the literature review among professional IT and security experts. Exploratory factor analysis (EFA) was carried out with IBM SPSS, and confirmatory factor analysis (CFA) was employed with IBM AMOS. This study proposed and developed a UAV-based SCM model to provide security for Qatar’s mega sporting events, which comprised five factors: traceability, security and privacy, trust, acceptability, and preparedness. This study also confirmed the validity and reliability of the newly developed scales, offering practical and proposed implications for the IT and security industries. The key findings of the study are: (1) a valid and reliable UAV-based cybersecurity framework for FIFA mega sporting events was developed; (2) five critical factors were identified, including traceability, security and privacy, trust, acceptability, and preparedness; (3) all factors were significantly and positively correlated, highlighting the complexity of managing security systems in mega sporting events. Other Information Published in: Drones License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/drones7090555